PENGARUH KINERJA DAN KOMPETENSI KARYAWAN TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI (Studi Empiris pada KSP Kopdit Tuke Jung, Desa Nelle Wutung-Kecamatan Nelle-Kabupaten Sikka) - Theresia Deby Susanti; Pipiet Niken Aurelia; Yoseph Darius Purnama Rangga (Universitas Nusa Nipa Maumere, 2025)
This study aims to examine the effect of employee performance and employee competence on the effectiveness of accounting information systems (AIS) at Koperasi Simpan Pinjam Tuke Jung. The research method applied is quantitative with a descriptive analysis approach. The data analysis techniques used include data quality tests, classical assumption tests, multiple linear regression analysis, hypothesis testing through t-test and F-test, as well as the coefficient of determination (R²). The sample of this study consisted of 40 employees of KSP Tuke Jung. The results indicate that employee performance has a positive and significant effect on the effectiveness of the accounting information system. Employee competence also has a positive and significant effect on the effectiveness of the accounting information system. Simultaneously, employee performance and competence have a positive and significant influence on the effectiveness of the accounting information system, as reflected in the coefficient of determination (R²), which shows the contribution of the independent variables to the dependent variable. Based on these findings, it can be concluded that improving employee performance and competence will enhance the effectiveness of the accounting information system implementation at KSP Tuke Jung.